Capital punishment in the Philippines - Johnson, David T. (The Elgar companion to capital punishment and society, 2024)
The Philippines is the only Christian nation in Asia, and the most Westernized one as well. In many ways it remains a feudal society dominated by a small oligarchy. This chapter describes and explains the main death penalty changes that have occurred in the country since 1987, when a new Constitution abolished the penalty after dictator Ferdinand Marcos was overthrown by the People Power movement. Six years later the Philippines resurrected capital punishment by enacting one of the most expansive capital statutes in Asia. By 1998, the country had condemned to death more than 1000 people, giving it one of the largest death rows in Asia, but only seven of those persons were executed (in 1999-2000: the Philippines’ first judicial executions since 1976). In 2000 an official moratorium on executions was declared, which lasted until Easter of 2006, when President Gloria Macapagal Arroyo commuted more than 1200 death sentences in what was then the largest capital commutation the world had ever seen. Two months later Arroyo signed legislation that abolished the death penalty in the Philippines for the second time in 20 years. Since then, there have been several more efforts to reinstate capital punishment, but none has succeeded. While the death penalty waxed and waned during the decades after Marcos was displaced, extrajudicial killing in the country continued. It surged greatly under President Rodrigo Duterte, whose “War on Drugs” (2016-22) resulted in the deaths of thousands (perhaps tens of thousands) of Filipinos. This study suggests several lessons about capital punishment in the modern world. The road to abolition is not necessarily straight and smooth. In some societies judicial killing is small potatoes compared to extrajudicial killing, so state killing might not decline after the death penalty is abolished. Impunity for crime is fertile ground for public support of state killing. And penal populism and governing through crime, which are common in developed and developing societies alike, are strategies of governance that help explain why state killing persists on a large scale in some societies.